RISK FACTORS OF PLACENTAL ABRUPTION - TATIANA Y. Marochko; MARIA N. Surina; DARIA K. Selezneva; SVETLANA Y. Khapacheva (Фундаментальная и клиническая медицина)
Aim. To identify the risk factors of placental abruption. Materials and Methods. We retrospectively investigated 80 case histories of women either with or without placental abruption (40 case histories per group) who delivered within 2011-2016 in Reshetova Kemerovo Regional Perinatal Center.Results. A number of risk factors of placental abruption has been identified including smoking (OR = 13.0, 95% CI = 1.6-107.2), placenta previa (OR = 7.4, 95% CI = 2.2-24.6), arterial hypertension (OR = 6.3, 95% CI = 1.3-31.1), uter-ine scar (OR = 6.3, 95% CI = 1.3-31.1), placental insufficiency (OR = 3.4, 95% CI = 1.0-11.8), and low level of education (OR = 2.9, 95% CI = 1.1-7.1). Other predictors were not statistically significant. Conclusions. Abovementioned risk factors of placental abruption should be considered in management of the pregnant women.